If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-29=8(w-8)-3w
We move all terms to the left:
-29-(8(w-8)-3w)=0
We calculate terms in parentheses: -(8(w-8)-3w), so:We get rid of parentheses
8(w-8)-3w
We add all the numbers together, and all the variables
-3w+8(w-8)
We multiply parentheses
-3w+8w-64
We add all the numbers together, and all the variables
5w-64
Back to the equation:
-(5w-64)
-5w+64-29=0
We add all the numbers together, and all the variables
-5w+35=0
We move all terms containing w to the left, all other terms to the right
-5w=-35
w=-35/-5
w=+7
| -7(-3y+1)-y=2(y-7)-5 | | 8x-(4x+3)=45 | | 11x-29=3x-15 | | 1/2(2x-4)=19-9x | | 5x-4=-4x+8 | | 3y-21=36 | | 25=3x+4(x+8) | | -2(3y-7)+2y=8+2(7y-3) | | 7x+5-3x=45 | | -33=-(z+15) | | -3v*9=30 | | 6(v-1)=6v+3-3(-4v-3) | | 230=-w+96 | | (x-4)/x-3=1 | | (9x-4)=(5x=16) | | 203-v=23 | | (x-4/x-3)=1 | | b+38/8=7 | | z/9+5-3=10-3 | | 6(u+4)=-4(4u-4)+6u | | 3/2n=-1/9 | | 156-y=211 | | c+6=-1 | | -3(-7+4)-9u=2(u-9)-2 | | 7(x+6)=-4(3x-7)+x | | 7(u+2)=70 | | (x-4)/(x-3)=1 | | -18+3h=69 | | -5(-5u+7)-6u=7(u-7)-2 | | |8x+9|=33 | | -7(j+2)=-84 | | -4(x+4)=7x-27 |